2012
DOI: 10.1037/h0100712
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus overselectivity: Empirical basis and diagnostic methods.

Abstract: This paper presents the empirical basis for the phenomena known as stimulus overselectivity. Stimulus overselectivity involves responding on the basis of a restricted range of elements or features that are discriminative for reinforcement. The manner for three different types of overselectivity: identical feature control, irrelevant feature control, and incomplete stimulus control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Second, the delivery of the IF in all learning trials may have hindered skill acquisition for secondary targets for Zoe and Samantha. The participants may have engaged in stimulus overselectivity, which is responding to stimuli based on restricted, incomplete, or irrelevant stimulus features (Cipani, 2012). Essentially, Zoe and Samantha may have responded to the most salient features (i.e., stimulus cards) to the exclusion of IF.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the delivery of the IF in all learning trials may have hindered skill acquisition for secondary targets for Zoe and Samantha. The participants may have engaged in stimulus overselectivity, which is responding to stimuli based on restricted, incomplete, or irrelevant stimulus features (Cipani, 2012). Essentially, Zoe and Samantha may have responded to the most salient features (i.e., stimulus cards) to the exclusion of IF.…”
Section: Discussionmentioning
confidence: 99%
“…Central to the design of effective educational programs is the ability to identify and modify sources of inaccurate or inconsistent responding. In the first article, Cipani (2012) provides a literature review of stimulus overselectivity, a phenomena that occurs when a learner responds to a restricted range of features of a compound stimulus. After a review of basic research on overselectivity, the article provides a diagnostic system for detecting error patterns that limit skill acquisition in discrimination learning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that blocking is likely related to stimulus overselectivity, in which some relevant properties of a compound stimulus fail to acquire stimulus control (e.g., Cengher, Budd, Farrell, & Fienup, 2018;Cipani, 2012;Farber, Dickson, & Dube, 2017;Lovaas, Schreibman, Koegel, & Rehm, 1971;Ploog, 2010). Such narrow attending may be maladaptive and is sometimes associated with children with autism (Dube et al, 2016;Lovaas et al, 1971).…”
mentioning
confidence: 99%